The role of financial literacy as a preparatory towards facing household financial crisis: the case for Japan - Ch’ng, Chin Xin; Liow, Kian Siang; Tan, Thye Huang; Toh, Mei Ting; Toh, Ming Fei (2021)
This study aims to determine the factors affecting household savings in Japan from year 1980 to 2018, which consists of annual data for 39 consecutive years. Similarly, this study will review past literatures completed by previous researchers in order to gain a more comprehensive understanding on the background of this research along with the issue that is concerning researchers about the financial literacy standards in Japan. The significance of this study to the policymakers and Japanese households will be emphasized. Apart from that, this study will also explore the extensive definitions of financial terms to clear the doubts of readers. A theoretical framework is constructed to investigate the relationship between household savings with the independent variables which are household debt, household spending and income tax as well as control variables which are inflation rate and economic growth rate. This study will focus on the Autoregressive Distributed Lag (ARDL) model by discussing on unit root testing method and the steps required to follow in order to run ARDL approach. Descriptive statistics will be applied to simplify the large amount of data while diagnostic checking will be used to ensure reliability of analyzed results. Furthermore, the results will be presented along with elaborated explanations for a complete understanding of the implemented methods and unbiased results obtained. This will be followed by a thorough discussion on the findings from this study in addition to the implications. Lastly, accompanying limitations will be recommendations suggested based on this study for future research which will highlight the elements that can be improved on.